THE IMPORTANCE OF HERMENEUTIC RESEARCH IN THE STUDY OF COMMUNICATION ETHICS (Universal International Scientific Journal, 2026)
This article examines the role of the use of hermeneutic research in philosophy in the scientific study of communication ethics, as well as important aspects of its cultural and social application. The article shows the prospects for using hermeneutics in the theoretical and practical substantiation of the process of communication based on ethical rules.
Keywords: hermeneutics, interpretation, ethics, communication ethics, understanding, social relations, communicativeness, philosophical approaches.